To find (f o g)(x) = f(g(x)), pick an x-value from g, find the corresponding y-value for g, plug this in as an x-value for f, and find the corresponding y-value for f. The first x-value and the second y-value correspond to a point for (f o g)(x).
I having major problems with these. Could someone please show me how to do them step by step.
For each ordered pairs, find f o g and g o f if they exist. (f of g and g of f )
5. F= {(0,0),(4,-2)}
G= {(0,4),(-2,0),(5,0)}
6. F = {(0,-3); (1,2), (2,2)}
G= {(-3,1), (2,0)}
7. F = {(-4,3), (-1,1), (2,2)}
G = {(1,-4),(2,-1),(3,-1)}
8. F = {(6,6),(-3,-3),(1,3)}
G = {(-3,6),(3,6),(6,-3)}